Three Methods of Preserving Guttural Consonants in the Tiberian Tradition: ṿayḳanʾû, ûzahav, harʿimah - Ariel, Chanan (Journal of Semitic studies, 2020)
This article identifies three methods of preserving the guttural consonants ʾ, h, ḥ and ʿ in the Tiberian tradition in sequences comprised of a non-guttural consonant, a guttural consonant, and a vowel: (a) geminating the consonant before the guttural consonant; (b) vocalizing this consonant with ḥatef; (c) omitting the gemination of the consonant prior to the guttural consonant. The article deals with the relationship between these three methods, and discusses forms that have been correctly described in the research literature alongside forms for which no convincing explanation has yet been offered. The unexplained forms are interpreted here in light of these identified methods.